Validação do Psychosocial Impact of Dental Aesthetics Questionnaire em adolescentes brasileiros na faixa etária de 11 14 anos - Paula Carolina Mendes Santos (2012)
Several instruments have been used to assess the oral-health-related quality of life (OHRQoL). The Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ) is a questionnaire that assesses the psychosocial impact of dental aesthetics and has been validated in Brazil for use on 18 to 30 years-olds. The aim of this study was to assess the validity and reliability of the Brazilian version of the PIDAQ for use on Brazilian adolescents aged 11 to 14 years. The questionnaire was completed by 194 adolescents (90 boys and 104 girls) enrolled at a public elementary school in the city of Belo Horizonte, Brazil. In order to test discriminant validity, subjects were examined for the presence or absence of malocclusion based on the Dental Aesthetic Index (DAI) criteria. Dental examinations were carried out by a previously calibrated examiner (inter-examiner weighted kappa = 0.58- 1.00; intraexaminer weighted kappa = 0.64- 1.00). Parents/guardians and adolescents who agreed to participate by signing a statement of informed consent were included in the study, which was approved by the Human Research Ethics Committee of the Federal University of Minas Gerais (109/08). The SPSS (version 17.0) was used for data analysis (p<0.05). The reliability was assessed through the internal consistency ( Cronbach's alpha 0.59 - 0.86) and the test-retest , measured by the intraclass correlation coefficient (ICC), which showed values greater than 0.8 for dental self-confidence, social impact and psychological impact thereby indicating a satisfactory reliability. The discriminant validity revealed a statistically significant difference between the mean scores for the domains of dental self-confidence and psychological impact among groups with and without malocclusion. The results showed that the Brazilian version of PIDAQ has satisfactory reliability for use in adolescents aged 11-14 years in Brazil.